Unemployment Durations in West-Germany Before and After the Reform of the Unemployment Compensation System During the 1980s - Bernd Fitzenberger; Ralf A. Wilke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper empirically analyzes the distribution of unemployment durations in West- Germany before and after the changes during the mid 1980s in the maximum entitlement periods for unemployment benefits for elderly unemployed. The analysis is based on the comprehensive IAB employment subsample containing register panel data for about 500.000 individuals in West Germany. We introduce two proxies for unemployment, since the data do not involve a precise economic definition of unemployment. We provide a theoretical analysis of the link between the durations of nonemployment and of unemployment durations between jobs. In our empirical analysis we find significant changes in the distributions of nonemployment durations for older unemployed individuals. At the same time, the distribution of unemployment durations between jobs did not change in response to the reforms. Our findings are consistent with an interpretation that many firms and workers used the more beneficial laws as a part of early retirement packages but those workers who were still looking for a job did not reduce their search effort in response to the extension of the maximum entitlement periods. This interpretation is consistent with a simulation of our theoretical model under economically plausible assumptions.
Keywords: J65; C24; J64; 330; definition of unemployment; duration analysis; unemployment insurance; Arbeitslosenversicherung; Reform; Flexible Altersgrenze; Arbeitslosigkeit; Dauer; Schätzung; Deutschland